Hematologia dos vertebrados: a série vermelha do sangue (Revista Brasileira Multidisciplinar, 2021)
Hematology comprises the study of blood and its components, such as red blood cells, white blood cells, platelets and plasma. In this study, the differences between the structures of vertebrate red blood cells and how each of these groups perform gas exchange and how oxygen transport occurs are indicated. The role of blood, responsible for the transport of nutrients, and gases, such as oxygen, and other components, such as hemoglobin, was highlighted. The objective was to evaluate the importance of blood and oxygen transport for humans and animals, as well as the differences in the red blood series in the vertebrate classes, their hematological characteristics and the role of hemoglobin in oxygen transport. The study pointed out that breathing is a process that consists of the absorption of oxygen from the environment and the elimination of carbon dioxide from the body, resulting from this aerobic process. The absorption of oxygen is essential for all classes of animals and its transport occurs through the hemoglobin molecule. In mammals, including humans, mature erythrocytes do not have nuclei, and are unable to reproduce, this allows the cell to have space to store hemoglobin and for erythrocytes to carry more oxygen; in birds, reptiles, amphibians and fish, mature red blood cells have a nucleus and because they have a nucleus, these cells have a fundamental characteristic, the ability to perform mitosis, which differentiates erythrocytes from mammals.